GSA: node failures tolerent spatial window query processing algorithm in wireless sensor networks - LIU Liang; QIN Xiao-lin; DAI Hua; SHEN Jia-jia (Tongxin xuebao)
A node failures tolerent spatial window query processing algorithm called GSA was proposed. The grid size parameter was studied and a grid-based data collection schedule scheme to avoid the message collisions in the process of data collection was proposed. Finally, the influence of node density, the probability of node failure, query region size on the success rate of a query and the influence of node density, query message size, sensed data size, query region size, the probability of node failure on energy consumption were analysed. Analytical and experimental results show that in most cases GSA outperforms IWQE.